Zingiber Neotruncatum T.L. Wu, K. Larsen & Turland Description New Recorded for Flora in Vietnam - Hung, Nguyen Danh; Hoi, Tran Minh; Sam, Ly Ngoc; Huong, Le Thi; Dai, Do Ngoc (VNU Journal of Science: Natural Sciences and Technology, 2021)
In this paper, we reported Zingiber neotruncatum as a new record for Vietnam. Voucher specimens were collected in Nghe An province (Pu Hoat Nature Reserve: Dong Van Commune), deposited in the Herbarium of the Biology, Vinh University. A detailed description and illustration are provided along with data on distribution, ecology, phenology and notices to the related species.